Integrated Black Soldier Fly Bioconversion and Biodrying for Community-Based Organic Waste Management: A Circular Economy Model in Kota Padang, Indonesia - Robby Jannatan; Resti Rahayu; Fadjar Goembira; Silvi Yuliani; Intan Cahaya Ramadhani; Yona Afriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Padang City produces over 660 tons of waste each day, and more than 60% of it is organic. Most of this ends up at the Air Dingin landfill, which has long exceeded its capacity and still operates through open dumping. While Black Soldier Fly (BSF; Hermetia illucens) larvae have attracted growing research attention as an organic waste processor, studies combining BSF bioconversion with biodrying (TOSS) and digital market development within a single community-scale program are scarce. This study reports the implementation and evaluation of such an integrated program, carried out with the Smarkgood Farmer Group in Kota Padang. Working through a participatory action framework, the team executed five sequential stages: partner identification, knowledge dissemination, technical training, technology application, and field mentoring. Key interventions included constructing BSF biopond units, providing a waste shredder calibrated to optimal larval substrate size, introducing the TOSS biodrying method for residual organic material, building a waste supply partnership with the Padang BSF Maggot Association (Agodang), and guiding the group through e-commerce onboarding. Following these interventions, the group operated a more functional and productive facility, maintained a stable organic waste supply, and actively sold products through online platforms. This program illustrates how science-based bioconversion technology, waste valorization, and digital market access can be combined into a community model that is practically transferable to other urban settings facing similar waste pressures.